1995
DOI: 10.1164/ajrccm.152.6.8520794
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of skin test reactivity to decrements in pulmonary function in children with asthma or frequent wheezing.

Abstract: We examined the relationship between skin test reactivity and level of FEV1 in a stratified random sample of U.S. children 6 to 12 yr of age with asthma or frequent wheezing, studied as part of the Second National Health and Nutrition Survey (NHANES II). Subjects were considered symptomatic if they reported asthma or wheezing. Spirometry was performed according to ATS standards. Skin test reactivity to Alternaria, Bermuda grass, cat, dog, house dust, mixed long and short ragweed, oak, and rye grass allergens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 0 publications
3
25
0
1
Order By: Relevance
“…These results support the hypothesis that indoor home allergens are involved in or are markers of greater asthma severity, playing an important role in the pathogenesis of the disease, probably early in life. (30) The analysis including atopic index data demonstrated the relationship between atopy intensity and asthma severity. However, when we consider that the proportion of patients with persistent loss of pulmonary function (i.e., 8.3%) was relatively small in comparison with the total number of asthma patients in our sample, the small number of patients with persistent loss (n = 8) makes it difficult to analyze the factors associated with this outcome.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These results support the hypothesis that indoor home allergens are involved in or are markers of greater asthma severity, playing an important role in the pathogenesis of the disease, probably early in life. (30) The analysis including atopic index data demonstrated the relationship between atopy intensity and asthma severity. However, when we consider that the proportion of patients with persistent loss of pulmonary function (i.e., 8.3%) was relatively small in comparison with the total number of asthma patients in our sample, the small number of patients with persistent loss (n = 8) makes it difficult to analyze the factors associated with this outcome.…”
Section: Discussionmentioning
confidence: 96%
“…(23) Therefore, there is evidence that structural changes are responsible for a varying degree of airway irreversibility, thereby contributing to the phenomenon of loss of pulmonary function, and that frequent exacerbations lead to a decline in pulmonary function, given that they perpetuate (19) demonstrated a significant correlation between the atopic index for indoor home allergens in childhood and the persistence of asthma into puberty. (19) Another study (30) reported associations between those allergens and reduced FEV 1 values in children aged 6-12 years. These results support the hypothesis that indoor home allergens are involved in or are markers of greater asthma severity, playing an important role in the pathogenesis of the disease, probably early in life.…”
Section: Discussionmentioning
confidence: 99%
“…Until age 13-14 years, the incidence and prevalence of asthma are greater among boys than among girls. [133][134][135][136][137][138][139][140][141][142] Studies through puberty 139,[143][144][145][146][147][148][149][150][151][152][153][154][155] have shown a greater incidence of asthma among adolescent and young adult females [133][134][135]156,157 and a greater proportion of males with remission of asthma. [136][137][138][139][140] Before age 12, boys have more severe asthma than girls, 142 with higher rates of admission to hospital.…”
Section: Sex and Gendermentioning
confidence: 99%
“…Nearly 90% of children with asthma have respiratory allergies, with indoor allergens, house dust mite, Alternaria, cockroach, or cat most closely associated with childhood asthma (28). In addition, a strong correlation exists between the number of positive skin tests in children and the severity of asthma (29). Finally, the intensity of exposure to house dust mite protein during infancy has been shown to lead to an earlier onset of asthmatic symptoms in children (30).…”
Section: Allergic Sensitization As It Relates To Asthmamentioning
confidence: 99%